Potential interaction between proton pump inhibitor and clopidogrel (Faculty of Medicine Universitas Indonesia, 2013)
Clopidogrel is an anti-platelet agent commonly used in patients with atherosclerotic cardiovascular (CV) disease. Although formerly considered safe, several studies reported that the use of clopidogrel may cause a significant increase in the rate of gastrointestinal (GI) bleeding. This adverse effect could be minimized by coadministration of proton pump inhibitor (PPI). However, since PPI and clopidogrel share the same metabolic pathway, it has been hypothesized that the administration of PPI following clopidogrel therapy may cause a reduction in its anti-platelet effect, thereby increasing the risk of CV events. Recent studies found no significant inhibition in the activation of clopidogrel by CYP2C19 with administration of PPI in vitro. Pharmacokinetic and pharmacodynamic studies, as well as clinical studies, reported conflicting results regarding the potential interaction between PPI and clopidogrel. Until now, the available study investigated the PPI-clopidogrel interaction are primarily observational. The COGENT study is the only prospective, placebo-controlled trial examined the PPI-clopidogrel interaction. This study revealed no significant increase in CV events in patients receiving PPI following clopidogrel therapy, compared to the control group. Though remains controversial, current expert consensus recommended the administration of PPI in patients receiving clopidogrel, particularly in high-risk patients. (Med J Indones. 2013;22:57-62) Keywords: Cardiovascular, clopidogrel, gastrointestinal, proton pump inhibitor